Bear or bear-dog? An enigmatic arctoid carnivoran from the late Eocene of Asia - Zhang, Xin-Yue; Bai, Bin; Wang, Yuan-Qing (Frontiers in Earth Science, 2023)
Records of Paleogene arctoids are very scarce in Asia, but there are abundant records in Europe and North America. Here, we report a new arctoid taxon, Lonchocyon qiui gen. et sp. nov., from the late Eocene Baron Sog Formation of the Erlian Basin, Inner Mongolia, China. It is the first report of relatively complete, large arctoid from the Erlian Basin. The new taxon is characterized by its overall large size, a deep mandible with a marginal process and a rudimentary premasseteric fossa, much reduced premolars including p4, sectorial carnassial m1 with basined talonid, and unreduced m2-3. Lonchocyon exhibits a combination of morphologies present in both amphicyonids and the early ursid hemicyonines. The mandibular force profiles suggest that Lonchocyon could have delivered powerful canine bites while subduing prey, like large felids do today, and it may have occupied a specialized ecological niche as a predator consuming both soft flesh and hard objects.